2014
DOI: 10.3390/pr2040753
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterisation of Fluid Mechanics in a Spinner Flask Bioreactor

Abstract: The spinner flask bioreactor has been widely used in in vitro cell culturing processes due to its superiority in providing a homogeneous culture environment compared to traditional culturing methods. However, there is limited understanding of the flow fields in these bioreactors, and optimum culture conditions are yet to be determined. This article presents the experimental characterization of the flow field within a spinner flask at varying speeds (10 RPM to 80 RPM) and impeller positions. An optical, non-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…Although the maximum liquid shear stress of 0.08 Pa at 9° and 20 rpm in our study is slightly lower than the results reported by Kalmbach's (0.13 Pa) in 2 L and 20 L Cellbags of WAVE Bioreactor TM at 7° and 15 rpm, the average shear stresses are comparable (<0.05 Pa) [34]. These results, are also similar to the range of Goodwin's results (0.05 ≈ 0.092 Pa) in the RWV [35], but are significantly lower than the shear stress reported in SFBs [36]. In Goodwin's study, the low shear environment in the RWV was identified as a key factor in promoting the formation of 3D aggregates composed of adherent cells grown on microcarrier surfaces.…”
Section: Influence Of Bioreactor Condition On Size Distribution Of Hmsupporting
confidence: 81%
“…Although the maximum liquid shear stress of 0.08 Pa at 9° and 20 rpm in our study is slightly lower than the results reported by Kalmbach's (0.13 Pa) in 2 L and 20 L Cellbags of WAVE Bioreactor TM at 7° and 15 rpm, the average shear stresses are comparable (<0.05 Pa) [34]. These results, are also similar to the range of Goodwin's results (0.05 ≈ 0.092 Pa) in the RWV [35], but are significantly lower than the shear stress reported in SFBs [36]. In Goodwin's study, the low shear environment in the RWV was identified as a key factor in promoting the formation of 3D aggregates composed of adherent cells grown on microcarrier surfaces.…”
Section: Influence Of Bioreactor Condition On Size Distribution Of Hmsupporting
confidence: 81%
“…This is an approximate 78% increase to the maximum measured shear during continuous agitation, however, remains fivefold lower than values reported in literature to impair stem cell proliferation and viability 26 . Ismadi et al investigated the flow dynamics within a spinner flask equipped with a paddle impeller with a large impeller to tank diameter ratio ( D / T = 0.87), and characterized shear stress levels comparable to those found in this work 42 . Due to the extremely sensitive nature of stem cells, although the levels of shear are not predicted to detrimentally impact upon cell proliferation, the varying levels of shear within the flow is most likely to be a contributing factor to the commitment of differentiation pathways, and could explain the increase in cell differentiation yields of iPSCs obtained by Samaras et al 2 for increasing dwell durations, T dwell = 500–1,500 ms.…”
Section: Resultssupporting
confidence: 64%
“…Interestingly, Ismadi et al studied the flow dynamics of a spinner flask, commonly used in stem cell culture, also equipped with a radial flow paddle impeller with a large impeller to tank diameter ratio, D / T = 0.87, and found two counter rotating vortices formed in the impeller blade's wake, where the upper vortex also displays positive axial displacement. In addition, this study looked at different impeller clearances and found the lower vortex became most dominant when the impeller clearance is highest and most similar to the configuration in this work with the flat‐bottomed vessel 42 …”
Section: Resultsmentioning
confidence: 71%
“…These effects have relevance to flows where wall-particle interactions are important. Examples include sedimentation tanks used in the chemical and mining industries, cells in blood vessels and micro-carrier beads in bioreactors (Gupta et al, 2014;Ismadi et al, 2014). Numerical modelling of bluff bodies would enable the prediction of the movement of these particles and their settling behaviour in the above stated applications.…”
Section: Introductionmentioning
confidence: 98%